A retrospective comparison of induction chemoimmunotherapy versus chemotherapy followed by concurrent chemoradiotherapy and consolidation immunotherapy in stage III non-small cell lung cancer - Zhao, Jing; Miao, Da; Zhou, Jiaqi; Guo, Siyu; Tang, Yang; Lan, Fen; Xia, Lixia; Zhang, Ting; Huang, Jian (Frontiers in Oncology, 2024)
BackgroundPatients with locally advanced non-small cell lung cancer (LA-NSCLC) usually bear high tumor burden and are not tolerated well to concurrent chemoradiation therapy (CRT) followed by consolidation immunotherapy. We investigated the feasibility of chemoimmunotherapy as induction therapy before CRT for LA-NSCLC.MethodsWe retrospectively analyzed data from 91 patients with unresectable stage III NSCLC treated with either induction chemoimmunotherapy or chemotherapy before CRT. Tumor responses, survival statistics, and toxic effects were compared. The dosimetric parameters of the RT protocol were evaluated. The primary endpoint was progression-free survival (PFS). The overall response (ORR), the depth of response (DpR) were accessed at the end of CRT (ORRinduc+CRT, DpRinduc+CRT) and induction therapy (ORRinduc, DpRinduc).ResultsThe median PFS (mPFS) were significantly longer in the chemoimmunotherapy induction group (13.5 months vs. 11.2 months; HR, 0.56; 95% CI, 0.32–0.97; p=0.036). The ORRinduc+CRT, median DpRinduc+CRT (mDpRinduc+CRT) and mDpRinduc were significantly higher in the chemoimmunotherapy induction group (ORRinduc+CRT, 84.0% vs. 65.9%, p=0.044; mDpRinduc+CRT, 49.5% vs. 39.0%, p = 0.012; mDpRinduc, 38.5% vs. 28.0%, p=0.044). Incidence of treatment-related adverse events (AE) was similar between groups, with myelosuppression being the most common grade ≥ 3 AE. Regarding radiotherapy, adopting a mapping strategy with a 5–8 mm margin for clinical tumor volume resulted in decreased radiation doses to critical organs in the chemoimmunotherapy induction group.ConclusionsChemoimmunotherapy induction therapy before CRT improves efficacy with comparable incidence of AEs compared to chemotherapy induction in LA-NSCLC patients. Further studies are warranted to validate these findings.